2021
DOI: 10.1177/0363546520988039
|View full text |Cite
|
Sign up to set email alerts
|

Forces at the Anterior Meniscus Attachments Strongly Increase Under Dynamic Knee Joint Loading

Abstract: Background: The anatomic appearance and biomechanical and clinical importance of the anterior meniscus roots are well described. However, little is known about the loads that act on these attachment structures under physiological joint loads and movements. Hypotheses: As compared with uniaxial loading conditions under static knee flexion angles or at very low flexion-extension speeds, more realistic continuous movement simulations in combination with physiological muscle force simulations lead to significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Previous studies have evaluated 1-dimensional PMMR forces in the setting of an ACL-deficient knee or during normal knee loading. 22,32,33,35 However, this study has demonstrated that, to stabilize the knee, the reaction forces in the PMMR are variable and multiaxial. Any assessment of the forces at the PMMR should include measurement of forces in all directions.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have evaluated 1-dimensional PMMR forces in the setting of an ACL-deficient knee or during normal knee loading. 22,32,33,35 However, this study has demonstrated that, to stabilize the knee, the reaction forces in the PMMR are variable and multiaxial. Any assessment of the forces at the PMMR should include measurement of forces in all directions.…”
Section: Discussionmentioning
confidence: 94%
“…Third, the MOWHTO was not surgically performed in vitro but simulated by adjusting the leg alignment by an altered CCD angle that resulted in a 10° valgus shift of the knee joint angle. Due to the combination of a slightly compromised stability of the knee joint, which was induced by soft tissue removal, and the high mechanical loads that result in realistic tibiofemoral contact pressures [39] that are applied to the knee joints could have led to lateral hinge fractures after MOWHTO surgery. In addition, it would not have been possible to clearly determine the cause of the obtained results, because the surgical interventions of the MOWHTO and the notchplasty could potentially influence each other.…”
Section: Discussionmentioning
confidence: 99%
“…This could be mainly attributed to the joint gap widening, and to the concurrently reduced contact pressure on the medial compartment, which appears to move the NUsurface ® device more compared to the normal leg alignment conditions [43]. The used knee joint simulator is able to perform dynamic loading situations on cadaveric knee joints that result in physiological tibiofemoral contact pressures [39]. Therefore, the contact pressure between the femur and tibia as well as the resulting contact transmission of the device in the present study could be assumed to be adequate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Meniscus root bears tension up to 200 N with a 20 mm 2 cross-sectional area 13,14 , in which the stress is comparable to using a single hand to lift a five-ton truck. The demanding mechanical loading regime drives the root-bone interface to evolve into an extremely tough, fatigue-resistant soft-hard transitional structure.…”
Section: Introductionmentioning
confidence: 99%